Penerapan Green Building pada Revitalisasi Pasar Raya Padang Fase VII oleh Dinas Perdagangan Kota Padang - Sri Rahayu Saputri; Rizki Syafril (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Revitalization of traditional markets aims not only to improve the quality of facilities but also to encourage sustainable management through the application of the Green Building concept. However, the implementation of this concept in traditional markets still faces various challenges. This study aims to analyze the application of Green Building in the revitalization of Pasar Raya Padang Phase VII, identify the obstacles encountered, and examine the efforts made to overcome them. The study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation of purposively selected informants, including the Padang City Trade Office, Pasar Raya Technical Implementation Unit (UPTD), traders, visitors, and WALHI West Sumatra. Data were analyzed using the Miles, Huberman, and Saldana model. The results show that the revitalization of Pasar Raya Padang Phase VII has integrated most of the Green Building principles, characterized by improvements in the quality of facilities, cleanliness, comfort, and more sustainability-oriented market management. However, its implementation has not been optimal due to constraints on inter-agency coordination, less than optimal utilization of facilities, low awareness of some traders, and limited management capacity. These findings confirm that the successful implementation of Green Building in traditional markets does not only depend on the provision of infrastructure, but also requires strengthening governance, collaboration between stakeholders, and increasing human resource capacity to ensure the sustainability of market management.